2018
DOI: 10.21203/rs.2.122/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CARer-ADministration of as-needed subcutaneous medication for breakthrough symptoms in homebased dying patients (CARiAD): study protocol for a UK-based open randomised pilot trial

Abstract: Background: While the majority of seriously ill people wish to die at home, only half achieve this. The likelihood of someone dying at home often depends on the availability of able and willing lay carers to support them. Dying people are usually unable to take oral medication. When top-up symptom relief medication is required, a clinician travels to the home to administer injectable medication, with attendant delays. The administration of subcutaneous injections by lay carers, though not widespread practice i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Trainings for lay carers, for example for subcutaneous as-needed doses, may reportedly play a key role in achieving adequately symptom controlled home deaths. 33 Additionally, previous studies have suggested educational training as well as simulation programs for professionals, especially regarding types of sedation that are only rarely performed. 21,34 In accordance with a previous study, our participants also stressed the value of shared documentation involving all relevant parties.…”
Section: Discussionmentioning
confidence: 99%
“…Trainings for lay carers, for example for subcutaneous as-needed doses, may reportedly play a key role in achieving adequately symptom controlled home deaths. 33 Additionally, previous studies have suggested educational training as well as simulation programs for professionals, especially regarding types of sedation that are only rarely performed. 21,34 In accordance with a previous study, our participants also stressed the value of shared documentation involving all relevant parties.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the international literature indicates that in other countries, particularly the United States and Australia, FCGs are regularly undertaking even more advanced tasks in administering sub-cutaneous medications prescribed for end of life symptoms [32][33][34][35][36]. While there have been some moves towards this in the UK the feasibility of this approach is still being assessed [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…While there have been some moves towards this in the UK the feasibility of this approach is still being assessed 38,39 .…”
Section: Discussionmentioning
confidence: 99%